Evaluación de riesgos de incendios en los cordones montañosos costeros de Chile Central - Quintanilla, Víctor (Geographicalia, 2017)
The effect of forestry wild fires on scrub and sclerophyllous vegetation in the mediterranean climate zone of Chile is studied, evaluating both the impact and recovering capacity. The study was carried out in the coastal ravines near Valparaíso-Viña del Mar cities. In the control area a phytogeographical shidy with the land survey and aerial photographic analysis wiyh 30 years covering. The main conclusions are: today four communities with different strategies of resistance to fire detected: the sclerophyllous forest to Cryptocaria alba and Peumuss boldus ("palma chilena") forest; the scrub of the Quillaja saponaria-litherena caústica vegetative sprout and long youthful phase and the semixeric scrubs to Puya coerulea-Trevoa trinervis. Litherena caústica arboreus species that recuperates best after fire. Quillaja saponaria, shows less recuperation owing to the effects of herbivory uppon its renewalls. Non afeccted by the fire Jubaea chilensis and Puya coerulea. The plant regeneration rate shrub and herbaceous stratum was lower than expected and the serious erosion processous we are detected. Jubaea chilensis istin this moment only in dangerous regeneration, by the sever slope the ravines. A important series of diacronic vegetation maps consists of the 1:50.000 sheets originally, prepared, and information abouth the use remote-sensing techniques to widland fire mangements is working.